Предмет: Алгебра, автор: 551002450129

ПОМОГИТЕ ПОЖАЛУЙСТА 2 ПРИМЕР)))))

Приложения:

Ответы

Автор ответа: emmettbrown
0
1. frac{2ab}{(a-b)(a+b)}+ frac{a-b}{2(a+b)}= frac{4ab+a^{2}-2ab+b^{2}  }{2(a-b)(a+b)}= \  \  frac{a^{2}+2ab+b^{2}  }{2(a-b)(a+b)}= frac{(a+b)^{2} }{2(a-b)(a+b)}= frac{a+b}{2(a-b)}  \  \ 2. frac{a+b}{2(a-b)}* frac{2a}{a+b}= frac{a}{a-b}      \  \ 3. frac{a}{a-b}- frac{b}{a-b}=1.
Автор ответа: 551002450129
0
спасибо большое
Похожие вопросы
Предмет: Қазақ тiлi, автор: ritashemet10082010